1990
DOI: 10.1104/pp.94.3.1323
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a 2-Oxoglutarate Dependent Dioxygenase Involved in the Second-to-Last Step in Vindoline Biosynthesis

Abstract: Young leaves from Catharanthus roseus plants contain the enzymes which convert the monoterpenoid indole alkaloid, tabersonine by three hydroxylations, two methylations, and one acetylation step to vindoline. A novel direct enzyme assay has been developed for a hydroxylase involved in vindoline biosynthesis, which catalyzes the C4-hydroxylation of 2,3-dihydro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
50
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 26 publications
(29 reference statements)
7
50
0
Order By: Relevance
“…They are involved in a broad spectrum of primary and secondary biosynthetic pathways including the post-translational hydroxylation of proline and lysine residues in procollagens (Kivirikko et al, 1989), the biosynthesis of carnitine ) and blood-coagulation-factor VII (Stenflo et al, 1989) in mammals, the conversion of thymidine into uracil (Holme et al, 1970(Holme et al, , 1971Bankel et al, 1977) and of penicillins into cephalosporins (Baldwin and Abraham, 1988) in bacteria and fungi, the biosynthesis of clavulanic acid (Elson et al, 1987) and the macrolide antibioticum tylosin (Omura et al, 1984) in fungi, the formation of hydroxyproline-rich glycoproteins in plants (Chrispeels, 1969;Tanaka et al, 1980) and the biosynthesis of plant secondary products such a5 flavonoids Britsch et al, 1981), the alkaloids scopolamine (Hashimot0 and Yamada, 1986) and vindoline (De Carolis et al, 1990) and gibberellins (Hedden and Graebe, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…They are involved in a broad spectrum of primary and secondary biosynthetic pathways including the post-translational hydroxylation of proline and lysine residues in procollagens (Kivirikko et al, 1989), the biosynthesis of carnitine ) and blood-coagulation-factor VII (Stenflo et al, 1989) in mammals, the conversion of thymidine into uracil (Holme et al, 1970(Holme et al, , 1971Bankel et al, 1977) and of penicillins into cephalosporins (Baldwin and Abraham, 1988) in bacteria and fungi, the biosynthesis of clavulanic acid (Elson et al, 1987) and the macrolide antibioticum tylosin (Omura et al, 1984) in fungi, the formation of hydroxyproline-rich glycoproteins in plants (Chrispeels, 1969;Tanaka et al, 1980) and the biosynthesis of plant secondary products such a5 flavonoids Britsch et al, 1981), the alkaloids scopolamine (Hashimot0 and Yamada, 1986) and vindoline (De Carolis et al, 1990) and gibberellins (Hedden and Graebe, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Severa1 enzymes and intermediates in this pathway have been characterized. These enzymes include an O-methyltransferase (Fahn et al, 1985b), an N-methyltransferase , a 2-oxoglutarate-dependent dioxygenase (De Carolis et al, 1990), and an O-acetyltransferase (De Luca et al, 1985;Fahn et al, 1985a). Most of the intermediates required for these enzymatic steps have been identified in etiolated seedlings De Luca et al, 1986).…”
mentioning
confidence: 99%
“…The final reaction is catalyzed by acetyl coenzyme A (CoA):deacetylvindoline 4-O -acetyltransferase (DAT;De Luca et al, 1985;Power et al, 1990). Some of these enzymes are not expressed in cell cultures or in tissues unable to produce vindoline De Carolis et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The final reaction is catalyzed by acetyl coenzyme A (CoA):deacetylvindoline 4-O -acetyltransferase (DAT;De Luca et al, 1985;Power et al, 1990). Some of these enzymes are not expressed in cell cultures or in tissues unable to produce vindoline De Carolis et al, 1990).It has been suggested that certain tissues are required for alkaloid biosynthesis and/or accumulation. Yoder and Mahlberg (1976) used chemical indicators to identify laticifers and "specialized parenchyma cells" as the sites of alkaloid accumulation in C. roseus.…”
mentioning
confidence: 99%
See 1 more Smart Citation